Sport and the Pursuit of War and Peace from the Nineteenth Century to the Present War Minus the Shooting? - Hurcombe, Martin; Dine, Philip (Routledge Studies in Cultural History, 2023)
Japan; cinema; soldier-athlete; victim; representation; sport